Single inhaler maintenance and reliever therapy in pediatric asthma. Issue 2 (April 2019) - Nalin, Ug; Stout, Sean; Portnoy, Jay M.
Abstract : Purpose of review: Asthma affects more than 25 million people worldwide and continues to grow in prevalence. According to a center for disease control and prevention (CDC) report, the total annual cost of asthma in the United States between 2008 and 2013, including medical care, absenteeism, and mortality, was 81.9 billion. Although the National Institute of Health guidelines recommend fixed inhaled corticosteroid (ICS) dosing, the 2008–2010 Medical Expenditure Panel Survey showed that asthma is still poorly controlled. Single inhaler maintenance and reliever therapy (SMART) offers a possible alternative management plan. This is a review of SMART vs. current treatment guidelines. Recent findings: SMART addresses variable inflammation with symptom-driven dosing of ICS. It relies on a combination inhaler that has a long-acting β-agonist, which has an immediate onset of action to provide quick relief, in combination with an ICS. Recent studies show that SMART decreases the frequency and severity of asthma exacerbations when compared to fixed ICS dosing. In addition, intermittent use of ICS gave a reduced effect on growth and permitted a lower total amount of ICS to be delivered. Summary: SMART appears to outperform treatment that is based on current guidelines in the United States. As inhalers capable of being used for SMART are already approved, what is needed is Food and Drug Administration approval of the SMART strategy.